2013
DOI: 10.3109/09687637.2013.806432
|View full text |Cite
|
Sign up to set email alerts
|

Legal and illegal drug use among female sex workers in bar and club prostitution in Belgium: A quantitative and qualitative study

Abstract: Aims: This study describes the amounts and effects of drug use in bar and club sex work, and the use of healthcare for the drug-related needs of sex workers (SW). Methods: A cross-sectional study was carried out in Belgium. In a quantitative component, 120 bar and club SW were interviewed face-to-face by means of a semi-structured questionnaire. In a qualitative component, 25 SW were interviewed face-to-face and 5 focus group discussions with key actors professionally involved with the study's subject were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Drug abuse is very common in the setting of prostitution: the prevalence of alcohol abuse among Belgian prostitutes was reported to be 88.4 %. During the survey, 18-20 % reported that they had consumed cannabis, cocaine or benzodiazepines in the past few weeks [26].…”
Section: Alcohol Abuse Tobacco and Drug Consumption Risk Of Infectionmentioning
confidence: 99%
“…Drug abuse is very common in the setting of prostitution: the prevalence of alcohol abuse among Belgian prostitutes was reported to be 88.4 %. During the survey, 18-20 % reported that they had consumed cannabis, cocaine or benzodiazepines in the past few weeks [26].…”
Section: Alcohol Abuse Tobacco and Drug Consumption Risk Of Infectionmentioning
confidence: 99%